2019
DOI: 10.1088/1674-1056/28/7/074203
|View full text |Cite
|
Sign up to set email alerts
|

Light propagation characteristics of turbulent plasma sheath surrounding the hypersonic aerocraft*

Abstract: The characteristics of light propagation through turbulent plasma sheath surrounding the hypersonic aircraft have been studied. The turbulent flow fields around a hypersonic aircraft are given by using the Navier–Stokes (NS) equations and k–ε turbulence model. Based on the distribution of flow field, refractive index and density of the plasma sheath for a blunt cone are discussed with different flight velocities and altitudes. The refractive index is mainly influenced by the electrons in the turbulent plasma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In this section, we review the power spectrum for PST based on which can be used for quantifying the interference of PST on the properties of the CPG vortex beam. Considering that PST is a turbulent shear flow with asymmetry and non-uniformity [23], the power spectrum of refractive index undulation can be characterized using the modified von Karman spectrum [24]…”
Section: The Refractive Index Fluctuation Power Spectrum Of Plasma Sh...mentioning
confidence: 99%
“…In this section, we review the power spectrum for PST based on which can be used for quantifying the interference of PST on the properties of the CPG vortex beam. Considering that PST is a turbulent shear flow with asymmetry and non-uniformity [23], the power spectrum of refractive index undulation can be characterized using the modified von Karman spectrum [24]…”
Section: The Refractive Index Fluctuation Power Spectrum Of Plasma Sh...mentioning
confidence: 99%
“…This occurs because of the friction between the spacecraft and the gas environment surrounding the aircraft. A turbulent plasma envelope formed around these spacecraft will affect the quality of communication between radars and spacecraft and sometimes cause communication interruptions [14]. Recently, several studies have been conducted on the propagation of different laser beams in turbulent plasmas [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used to analyze electromagnetic wave transmission characteristics in plasma, such as through using the Wentzel-Kramer-Brillouin (WKB) method, scattering matrix method (SMM), finite-difference time-domain (FDTD) method. [14][15][16][17][18][19][20][21][22][23][24][25] Yu et al used the WKB method to study the transmission characteristics of terahertz waves in magnetized plasmas with different electron density distributions. [26] Numerical simulation results demonstrated that the plasma density, plasma slab thickness, plasma density models, and collision frequency significantly influence the attenuation and transmittance of terahertz waves.…”
Section: Introductionmentioning
confidence: 99%